Sildenafil induces browning of subcutaneous white adipose tissue in overweight adults - Li, Shuguang; Li, Yixiang; Xiang, Lin; Dong, Jing; Liu, Min; Xiang, Guangda (Metabolism, clinical and experimental, 2018)
To investigate that short-term treatment of sildenafil can induce browning of subcutaneous white adipose tissue (sWAT) in human adults. A randomized, double-blinded, placebo-controlled, parallel group trial. Sixteen eligibility overweight male subjects were recruited, comparing 100mg/day sildenafil versus an identical placebo therapy for 7days. sWAT samples were collected from subjects before and after 7-day sildenafil or placebo interventions. The results showed that multilocular UCP1-positive adipocytes existed in sWAT samples from subjects after sildenafil treatment. Compared to before treatment in both group as well as after treatment in placebo, sildenafil significantly decreased adipocyte size, increased the expressions of UCP1 protein and mRNA, mitochondrial density, and leak respiratory capacity in sWAT (p<0.05). Sildenafil also increased plasma cyclic guanosine-3′,5′-monophosphate (cGMP) and catecholamine concentrations (p<0.05), and consequently activated the expressions of vasodilator-stimulated phosphoprotein (VASP) and p70 ribosomal S6 kinase 1 (S6K1) (p<0.05). Sildenafil did not activate typical brown fat. The current findings demonstrate that sildenafil can induce browning of sWAT in human, and this action may be through cGMP-dependent protein kinase I and mechanistic/mammalian target of rapamycin (mTOR) signaling pathways. Sldenafil may be a promising treatment for metabolic disease.